On the design of shear-strengthened RC members through the use of textile reinforced mortar overlays - Tetta, Zoi C.; Triantafillou, Thanasis C.; Bournas, Dionysios A. (Composites. Part B, Engineering, 2018)
Textile reinforced mortar (TRM) is a promising alternative to the FRP retrofitting solution for shear strengthening of reinforced concrete (RC) beams, based on the experimental results presented so far in the literature. Thus, the development of reliable and accurate design models for shear strengthening of concrete members with TRM is required for enabling their wider use in real applications. The available experimental data in the literature are limited and in most cases, a detailed description of the failure modes observed in the TRM jackets and information related to the characteristics of the textile material and the mortar strength are missing, complicating the development of design guidelines. In this paper, a design model to calculate the contribution of the TRM jacket to the total shear resistance was developed using all the well reported available data that were grouped based on the observed failure modes. Specifically, local damage of the jacket including slippage of the fibres through the mortar constitutes a recurring failure mode in concrete beams strengthened in shear with TRM jackets, apart from debonding of the jacket from the concrete substrate including peeling-off of the concrete cover or fracture of TRM jacketing that are also observed in case of fibre reinforced polymer (FRP) jacketing. The key parameters affecting each failure mode were defined and design formulations to calculate the contribution of the TRM jacket to the total shear resistance of RC beams for each failure mode were suggested, whereas a criterion indicating when each failure mode is possible to be observed was also set for using the proper formulation for each TRM system.